Determinant Factors Toward Bank Syariah Indonesia (BSI) Customer Loyalty: An Empirical Approach - Sulistyandari, Sulistyandari; Kusumah, Alum; Nofirda, Fitri Ayu (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (Adpebi), 2022)
This study examines the effect of Determinant Factors on Bank Syariah Indonesia's (BSI) Customer Loyalty and falls into the quantitative research area. The customers of Bank Syariah Indonesia (BSI) Riau are the sample for this study. The number of samples used in this study was 200, which met the standards. The data was gathered through the distribution of questionnaires, and the secondary data consisted of data or documents that supplemented and enhanced the primary data from books, magazines, journals, and other sources. The WarPLS 7.0 program performs data analysis using Structure Equation Modeling (SEM). Loyalty is the dependent variable in this study, while service quality and trust are the independent variables. These variables assess using a Likert scale using a 1-5 scale to evaluate the indicators of each variable. The results reveal no positive and significant effect between service quality and customer loyalty. However, there is a positive and significant effect between customer loyalty and trust. The study results add to the academic literature, mainly by providing new discussions about theories and literature related to the Determinants of Customer Loyalty Factors in Indonesian Islamic Banks (BSI), which is infrequent.